ANALISIS KRISIS DEMOKRASI DI ISRAEL: STUDI KASUS REFORMASI YUDISIAL ISRAEL OLEH BENJAMIN NETANYAHU PADA TAHUN 2023 - Alayda Amir, Namira Syarafina (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
This study aims to analyze the democratic crisis in Israel in 2023 through the case study of the judicial reform proposed by Prime Minister Benjamin Netanyahu. The research highlights how the reform became an instrument to strengthen executive power while weakening the Supreme Court, and how Netanyahu’s personal factors, including his corruption cases, influenced Israel’s domestic and foreign policies, particularly towards Palestine. This research employs a qualitative method with a library research approach. The theory of Competitive Authoritarianism is used to explain Netanyahu’s consolidation of power within a formal democratic framework, while Operational Code theory is applied to trace Netanyahu’s philosophical and instrumental beliefs that emphasize military power over diplomacy. The findings reveal that the judicial reform represents Netanyahu’s authoritarian character as a strong man who seeks to undermine the judiciary for political and personal interests. This democratic crisis has led to polarization within Israeli society, intensified domestic conflicts, and increasingly aggressive foreign policies toward Palestine, especially after the October 7, 2023 attacks. Furthermore, the reform triggered international criticism and worsened Israel’s reputation as a democratic state in the eyes of the global community.